Investigation of sport participation motivation and psychological resilience in football players - Hamza Kucuk (Ozlem Book Center, 2024)
This study aims to examine the motives for participation in sports and the psychological resilience of soccer players.  A total of 351 volunteer football players who had been actively playing football for at least 5 years participated in the study. Psychological resilience scale for adults and sport participation motivation scale were used as data collection tools in the study.  According to the study results, those aged 18-21 use different sports participation motives. There are differences between age groups in psychological resilience sub-dimensions. A high relationship was found between the sub-dimensions of sport participation and psychological resilience sub-dimensions. This correlation may be due to the team unity of football players. When the differences between the positions are analysed, there are differences in the sub-dimensions of sports participation and psychological resilience. These differences can be related to the position and abilities of the players due to the game structure.